2020
DOI: 10.3389/fonc.2020.01344
|View full text |Cite
|
Sign up to set email alerts
|

lnc-REG3G-3-1/miR-215-3p Promotes Brain Metastasis of Lung Adenocarcinoma by Regulating Leptin and SLC2A5

Abstract: This study aims to explore the role and mechanism of specific lncRNA in brain metastasis (BM) from lung adenocarcinoma (LADC), providing an effective biomarker for early diagnosis and targeted therapy of BM from LADC. Based on the gene expression profiles of lncRNA and mRNA in LADC and BM tissues detected by Gene Chip, lnc-REG3G-3-1 was selected, and the related genes, including miR-215-3p, leptin, and SLC2A5, were identified by data analysis. Human LADC cell lines A549 and H1299 were cultured. Dual-luciferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In summary, the expression of specific lncRNAs has been reported to be correlated with clinical features in LAD, and the utility of lncRNAs in the diagnosis and prognosis of LAD has significant clinical value (33,34,55). In this study, we demonstrated that AC122108.1 was significantly upregulated in LAD BM cells and tissues, and that the expression of AC122108 was correlated with the malignancy of tumors, including tumor proliferation, apoptosis, invasion, migration, and metastasis.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…In summary, the expression of specific lncRNAs has been reported to be correlated with clinical features in LAD, and the utility of lncRNAs in the diagnosis and prognosis of LAD has significant clinical value (33,34,55). In this study, we demonstrated that AC122108.1 was significantly upregulated in LAD BM cells and tissues, and that the expression of AC122108 was correlated with the malignancy of tumors, including tumor proliferation, apoptosis, invasion, migration, and metastasis.…”
mentioning
confidence: 57%
“…Previous studies have shown that lncRNAs participate in the progression of human cancers, and can serve as biomarkers and therapeutic targets for tumors (30). As hallmarks of LAD, migration, invasion, and metastasis are regulated by lncRNAs (31,32), and many lncRNAs also play a critical role in LAD BM (33,34). Initially, lncRNA was considered to be RNA without biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of miR-215-3p leads to higher cell viability, migration, invasiveness, and expression of leptin and solute carrier family 2 member 5 (SLC2A5), followed by significant upregulation of VEGF, serine/threonine/tyrosine interacting like 1 (STYXL1), and flavin adenine dinucleotide synthetase 1 (FLAD1) mRNA levels and downregulation of Akt, phosphoinositide 3-kinase (PI3K), and sex-determining region-box transcription factor 4 (SOX4) mRNA levels. Higher leptin expression plays a crucial role in the promotion of metastases, especially due to the activation of the mammalian target of rapamycin (mTOR) pathway [ 123 ].…”
Section: Micrornas Involved In Brain Cancer Metastasesmentioning
confidence: 99%
“…The study also provided evidence that leptin-induced malignancies were driven through the activation of the ERK signaling axis [ 76 ]. In a study of brain metastasis of lung adenocarcinoma, activation of leptin signaling was highlighted in the context of the lnc-REG3G-3-1 high /miR-215-3p low axis [ 77 ]. The assessment of leptin drug resistance showed that bone marrow-derived mesenchymal stem cells could release leptin to induce erlotinib resistance in lung adenocarcinoma cells by activating IGF-1R signaling in a hypoxic environment, suggesting a predictive role of leptin expression for therapeutic response [ 78 ].…”
Section: Lep Somatic Mutations and Cancermentioning
confidence: 99%
“…↑: [67,70] ↑: [67] ↓: [66] Lung Cancer ↑: [79,80] ↑: [76,77,80] ↑: (erlotinib) [78], (cisplatin) [79] Pancreatic Cancer ↑: [82,87,88] ↑: [83] ↑: (gemcitabine) [86], (5-FU) [87] Prostate Cancer ↑: [89] ↑: [89,90] ↓: [89] Gallbladder cancer ↑: [91] Myeloma ↑: (bortezomib) [92] Chondrosarcoma ↑: [93,94] ↑: increase.↓: decrease.…”
Section: Colorectal Cancermentioning
confidence: 99%